Twelve stone slab fragments of hero stones and sculptures - Temples of India Project Team (Jio Institute, 2024)
Twelve stone slab fragments of hero stones and sculptures are placed on a low pedestal. People worship the stones of the brave souls and offer grains and sweets, after smearing them with vermilion. The stone fragments are often rubbed with oil, which has seeped into the incisions of the inscriptions. Due to continuous worship, the intricate details of the slabs are lost.